BRG1 interacts with SOX10 to establish the melanocyte lineage and to promote differentiation. Issue 11 (20th April 2017) - Marathe, Himangi G.; Watkins-Chow, Dawn E.; Weider, Matthias; Hoffmann, Alana; Mehta, Gaurav; Trivedi, Archit; Aras, Shweta; Basuroy, Tupa; Mehrotra, Aanchal; Bennett, Dorothy C.; Wegner, Michael; Pavan, William J.; et al.
Abstract: Mutations in SOX10 cause neurocristopathies which display varying degrees of hypopigmentation. Using a sensitized mutagenesis screen, we identified Smarca4 as a modifier gene that exacerbates the phenotypic severity of Sox10 haplo-insufficient mice. Conditional deletion of Smarca4 in SOX10 expressing cells resulted in reduced numbers of cranial and ventral trunk melanoblasts. To define the requirement for the Smarca4 -encoded BRG1 subunit of the SWI/SNF chromatin remodeling complex, we employed in vitro models of melanocyte differentiation in which induction of melanocyte-specific gene expression is closely linked to chromatin alterations. We found that BRG1 was required for expression of Dct, Tyrp1 and Tyr, genes that are regulated by SOX10 and MITF and for chromatin remodeling at distal and proximal regulatory sites. SOX10 was found to physically interact with BRG1 in differentiating melanocytes and binding of SOX10 to the Tyrp1 distal enhancer temporally coincided with recruitment of BRG1. Our data show that SOX10 cooperates with MITF to facilitate BRG1 binding to distal enhancers of melanocyte-specific genes. Thus, BRG1 is a SOX10 co-activator, required to establish the melanocyte lineage and promote expression of genes important for melanocyte function.